2022
DOI: 10.1088/1361-6463/ac708d
|View full text |Cite
|
Sign up to set email alerts
|

Isolation enhancement in dual-band MIMO antenna by using metamaterial and slot structures for WLAN applications

Abstract: A dual-band MIMO antenna with enhanced isolation operating in 2.35-2.50 GHz and 5.13-5.88 GHz bands is investigated and presented. The proposed antenna system is deformed from two inverted-F antennas, and the distance between the antenna elements is only 0.104λ (λ- wavelength of 2.4 GHz). To enhance isolation and reduce mutual coupling, the metamaterial and slot structures are efficiently and innovatively designed on the ground plane for two bands. Both decoupling methods effectively improve the antenna isolat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…There are different types of antennas (spiral wire, reflective horn, phased array, microstrip, etc). MIMO (multi-input, multi-output) is a wave propagation technology (antenna) for wireless telecommunication systems, and it has found a special place in wireless telecommunications due to the significant increase in data throughput and telecommunication link range, without the need for additional bandwidth or additional transmission power [1][2][3][4]. If the antennas are placed next to each other in an array [5] (both in receiver and transmitter modes), an undesired coupling occurs between the two antenna radiators elements, due to the reciprocal coupling of electric fields [6] which is induced from the first radiating element to the second radiating element and causes current to flow on the second radiating element, which is called the undesired electromagnetic coupling effect of the reciprocating coupling [7].…”
Section: Introductionmentioning
confidence: 99%
“…There are different types of antennas (spiral wire, reflective horn, phased array, microstrip, etc). MIMO (multi-input, multi-output) is a wave propagation technology (antenna) for wireless telecommunication systems, and it has found a special place in wireless telecommunications due to the significant increase in data throughput and telecommunication link range, without the need for additional bandwidth or additional transmission power [1][2][3][4]. If the antennas are placed next to each other in an array [5] (both in receiver and transmitter modes), an undesired coupling occurs between the two antenna radiators elements, due to the reciprocal coupling of electric fields [6] which is induced from the first radiating element to the second radiating element and causes current to flow on the second radiating element, which is called the undesired electromagnetic coupling effect of the reciprocating coupling [7].…”
Section: Introductionmentioning
confidence: 99%
“…The decoupling network was reported in [16,17]. In addition, several studies on metasurfaces have been reported in [18][19][20]. The content of these researches can only improve the coupling of single frequency point or narrow band, which can not provide good universality for the design of broadband MIMO antenna.…”
Section: Introductionmentioning
confidence: 99%